Sunburst appearance in odontogenic myxoma of mandible: A radiological diagnostic challenge - Sahil Mustafa Kidwai; Ravi Prakash Sasankoti Mohan; Vijay Wadhwan; Nagaraju Kamarthi; Sumit Goel; Swati Gupta (Journal of Oral and Maxillofacial Radiology, 2016)
Odontogenic myxoma in the jaws is infrequent, accounting for only 3%-6% of odontogenic tumours. The radiological appearance of this tumor is complicated and there exist controversies regarding its internal structure and locularity. The "sunray" or "sunburst" appearance in Odontogenic myxoma has been reported in the literature although rarely. Here we report a case of odontogenic myxoma in the mandible showing sunburst appearance which posed a diagnostic dilemma for the oral radiologists. We also emphasize the usefulness of Cone Beam Computed Tomography in the diagnosis of such lesions.